OPTICAL STUDIES OF PENICILLIN GROUP IN RELATION TO THEIR MEDICAL ACTIVITY - R. Jeevan Kumar; G.V.R. Prasad; S.Md. Shoaib; G. Paul Devadanam; K. Fakruddin (Universitas Gadjah Mada, 2007)
The study of Medical activity of antibiotics is gaining momentum now a days owing to the importance of their curative values. The Medical Activity correlated to molecular interactions,can be studied by various physical techniques, at present optical methods like Refractometry and Polarization are used to study the activity of a few antibiotics like Penicillin. The Refractive Indices Mean Molecular Polarizability Diamagnetic Susceptibilities and Electron Ionisation Cross Section are interpreted in terms of dosages and the toxic effects if any due to over dosages are discussed critically.